Clinical Profile and Outcome of Japanese Encephalitis in Children Admitted with Acute Encephalitis Syndrome. (29th December 2013) - Kakoti, Gitali; Dutta, Prafulla; Ram Das, Bishnu; Borah, Jani; Mahanta, Jagadish
Abstract : Japanese encephalitis (JE) is an arthropod borne viral disease. Children are most commonly affected in Southeast Asian region showing symptoms of central nervous system with several complications and death. The clinical characteristics and outcomes in pediatric JE patients hospitalized with acute encephalitis syndrome (AES) are still poorly understood. A prospective study was conducted in pediatric ward of Assam Medical College Hospital to evaluate the clinical profile and outcome of JE in children. A total of 223 hospitalized AES cases were enrolled during March to December 2012. Serum and cerebro spinal fluids were tested for presence of JE specific IgM antibody. 67 (30%) were found to be JE positive. The most common presenting symptoms in JE patients were fever (100%), altered sensorium (83.58%), seizure (82.08%), headache (41.79%), and vomiting (29.85%). Signs of meningeal irritation were present in 55.22% of cases. Around 40.29%, JE patients had GCS ≤ 8. Among the JE patients, 14.7% died before discharge. The complete recoveries were observed in 63.9% of cases, while 21.3% had some sort of disability at the time of discharge. JE is still a major cause of AES in children in this part of India. These significant findings thus seek attentions of the global community to combat JE in children.